Pembinaan Kemampuan Profesional Guru di Sekolah dan Pengaruhnya Terhadap Kemampuan Mengajar Guru - Bambang Budi Wiyono; Maisyaroh Maisyaroh (Universitas Negeri Malang, 2016)
The present article reports on a research project investigating teachers' level of abstraction ability, commitment, and teaching skills. The research was also aimed to see the relationship between different frequencies of supervision on teachers and the teachers' teaching ability. The population included teachers at Primary Schools, Junior High Schools, Senior High Schools, and Vocational Schools in Malang. The sample, consisting of 20 schools and 84 teachers, was selected using cluster random sampling. The data, collected using questionnaire and through observations, were treated employing descriptive, correlational, and regression analyses. The research found that the teachers had an adequate level of abstraction ability. They also had sound commitment and teaching skills. The results also disclose that the most frequently used supervision techniques were collaborative and directive techniques. With regard to the frequency of the supervision, it was found to be adequate. The supervision frequency also correlated positively with the teachers' teaching skills.